Root-supported overdenture in a patient with a cleft palate and extensive bone loss after traumatic injury - Takeshita, Rodrigo Shinichi; Bento, Victor Augusto Alves [UNESP]; Castillo, Daisilene Baena (My University, 2023)
Maxillofacial trauma caused by automobile accidents can result in extensive loss of alveolar bone, teeth, and gingival tissues as well as a cleft palate. Patients who have undergone such trauma may experience a loss of vertical dimension of occlusion, esthetic deformity, and difficulties in speaking, chewing, and swallowing. Both prosthodontic and surgical treatment are required in these cases. This case report describes the use of palatoplasty and maxillary and mandibular complete overdentures with a ball attachment system supported by natural roots as rehabilitative treatment for a 65-year-old man who had been injured in an automobile accident 24 years previously. Palatoplasty was performed to close the cleft palate that resulted from the trauma. Other procedures, including tooth extractions, endodontic treatment, cementation of ball attachments, and fabrication of temporary removable partial dentures to reestablish the vertical dimension of occlusion, were performed before the overdentures were placed. This treatment reestablished the patient’s chewing, phonetic, and esthetic functions at a lower cost than other treatment options. At the 1-year followup evaluation, the patient’s oral health was satisfactory with no loss of abutment teeth, and the prostheses were functioning correctly.
Keywords: cleft palate; maxillofacial injuries; overdenture; quality of life; removable partial denture